(untitled) (International Journal of Ayurveda and Pharma Research, 2023)
The Siddha system is a primordial system of medicine followed over a long period in the Southern part of India. Siddha system has peculiar methods in treating a disease and also possesses various diagnostic methods and treatment protocols. In the Siddha system, diagnostic methods are purely differing from other systems. The diagnostic tools are Envagaithervu (Eight Fold Assessment Test), Neer Kuri & Nei Kuri (Siddha Urine Test), Nadi (Pulse Test) etc. In the Siddha system treatments are based on Nadi, Suvai. Diabetics are the major non-communicable disease in the world. According to the statistics India is second among the top ten nations in the world, with 69.2 million people suffering from diabetes and another 36.5 million struggling with pre-diabetes. This rising prevalence is mostly due to changes in lifestyle, such as consuming unhealthy foods and being physically sedentary. In the Siddha system, it is compared with Neerizhuvu Noi. In Siddha, diabetes is not an illness. It is possible to keep it under control with the right diet and treatment. The article focus on scientific justification of the relationship of herbs cured Neerizhuvu Noi mentioned in classical text by their organoleptic characters and anti diabetic activity of the herbs. Taste plays a significant part in the selection of medicinal plants for each person in this kind of personalized treatment that is based on their constitution. This article discusses the Siddha approach to the control of diabetes, with a particular focus on the flavour of herbs.